2021
DOI: 10.23822/eurannaci.1764-1489.132
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between disease activity, autoimmunity and biological parameters in patients with chronic spontaneous urticaria

Abstract: Background: Biomarkers of disease activity/severity and criteria of autoimmune chronic spontaneous urticaria (CSU) are still a matter of debate. Objective: To investigate possible correlations between clinical and biological markers and their associations with: (i) disease activity; (ii) resistance to H1-antihistamines; (iii) autoimmunity; and (iiii) autologous serum skin test (ASST) in patients with CSU. To also analyze biological parameter modifications in patients with CSU treated with omalizumab. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 34 publications
4
49
0
Order By: Relevance
“…Ma et al demonstrated that plasma levels of D-dimer were associated with disease activity of ANCA-associated vasculitis [34]. A prospective study conducted on patients with chronic spontaneous urticaria has reported that patients with autoimmune status had higher levels of plasma D-dimer than those without autoimmunity [35]. Weinberg et al reported that there were higher levels of D-dimer in the synovium of patients with RA than that in patients with OA and traumatic joint abnormalities [36].…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al demonstrated that plasma levels of D-dimer were associated with disease activity of ANCA-associated vasculitis [34]. A prospective study conducted on patients with chronic spontaneous urticaria has reported that patients with autoimmune status had higher levels of plasma D-dimer than those without autoimmunity [35]. Weinberg et al reported that there were higher levels of D-dimer in the synovium of patients with RA than that in patients with OA and traumatic joint abnormalities [36].…”
Section: Discussionmentioning
confidence: 99%
“…Rates of concomitant autoimmune diseases tend to be higher in type IIb [25,[118][119][120][121] Rates of concomitant allergic diseases might be higher in type I [119] Total IgE levels low in type IIb and normal or high in type I [14,25] Basopenia rates might be higher in type IIb [24, 111] 2 Eosinopenia rates tend to be higher in type IIb [122] C-reactive protein levels may be higher in type IIb [25,123] ANA positivity rates may be higher in type IIb [124] Responder rates to sgAHs may be lower in type IIb [122][123][124][125] Responder rates to omalizumab high in type I [28] and low in type IIb [62,122,126] Speed of response to omalizumab slow in type IIb [127] Immunosuppressive therapy can be effective in type IIb [128-134] 3 TPO, thyroperoxidase; TG, thyroglobulin; TF, tissue factor; IL, interleukin; dsDNA, double-stranded DNA; BHRA, basophil histamine release assay; BAT, basophil activation test; ASST, autologous serum skin test; WB, Western blot; ELISA, enzyme-linked immunosorbent assay; CRP, C-reactive protein; ANA, antinuclear antibodies; sgAHs, second-generation antihistamines. 1 Measured by ELISA or radioimmunoassay.…”
Section: Type I and Type Iib Autoimmunity: Emerging Endotypes Of Chromentioning
confidence: 99%
“… 17 Mean IgE values in CSU patients vary from 66 to 1,037 IU/mL ( Supplementary Table S1 ), regardless of whether comorbid atopic dermatitis was excluded. 18 19 The highest levels of IgE were found in atopic patients with CSU, 20 CSU with concomitant gastroesophageal reflux disorder, 21 and CSU patients with high interleukin (IL)-33 serum levels, 22 indicating that atopic status and concomitant disorders may influence serum total IgE levels of CSU patients.…”
Section: Are Total Serum Ige Levels Elevated In Csu?mentioning
confidence: 99%